Researchers' approaches to stakeholders: Interaction or transfer of knowledge?. Issue 97 (July 2019) - Knaggård, Åsa; Slunge, Daniel; Ekbom, Anders; Göthberg, Maria; Sahlin, Ullrika
Highlights: Environmental researchers understand stakeholder interaction in different ways. Confusion about this could impede stakeholder's use of scientific knowledge. Interaction is seen as a threat to scientific integrity or as enabler of studies. The study contributes knowledge about interaction to research and practice. Abstract: Stakeholder interaction is important for enabling environmental research to support the societal transition to sustainability. We argue that it is crucial to take researchers' approaches to and perceptions of stakeholder interaction into account, to enable more clarity in discussions about interaction, as well as more systematic interaction approaches. Through a survey and focus group interviews with environmental researchers at three Swedish universities, we investigate the effects of two models of stakeholder interaction, as well as high and low levels within each. The 'transfer model' implies that interaction is understood as communication and should be separated from research. The 'interaction model' implies that interaction happens throughout the research process. Our study shows some significant differences between researchers in the two models, but also between high and low levels of stakeholder interaction regardless of model. The result indicates that the transfer model needs to be considered in studies and practice of stakeholder interaction, but also that the low levels of the interaction model consists of a number of different types of approaches. The major difference between the two models was about how large researchers understood the benefits and risks with stakeholder interaction to be. Transfer researchers saw interaction as a threat to the integrity of research, whereas interaction researchers saw it as enabling research.